79.8k views
5 votes
Complete the equation.
(4x)−2(4x)3(4x)9=(4x)

1 Answer

7 votes

Given:

Consider the given equation is


(4x)^(-2)(4x)^3(4x)^9=(4x)^?

To find:

The missing value in the given equation and complete the equation.

Solution:

We have,


(4x)^(-2)(4x)^3(4x)^9=(4x)^?

Taking LHS, we get


LHS=(4x)^(-2)(4x)^3(4x)^9


LHS=(4x)^(-2+3+9)
[\because a^ma^n=a^(m+n)]


LHS=(4x)^(10)

and,


RHS=(4x)^?

Let the missing value be k.

For each equation LHS=RHS.


(4x)^(10)=(4x)^(k)


10=k

Therefore, the missing value is 10 and the complete equation is
(4x)^(-2)(4x)^3(4x)^9=(4x)^(10).

User Allen Rohner
by
4.8k points